INNOVATIONAL EDUCATIVE METHODS IN THE EDUCATIONAL SYSTEM (Modern education and development, 2024)
New information and qualifications are continually being added to the educational landscape of the modern world. New areas of interaction and specialties that comprise new disciplines are developing. Reforms are being made to higher education worldwide. The hunt for new educational technology and formats resulted from this. Higher education is developed in accordance with a number of guiding concepts in order to align with global norms and criteria. First and foremost, this is the introduction of novel achievements in science and education. It is well recognized that the creation of a generation of people who are creative depends on the innovative ways in which society develops. The development of personality, cultural and communicative preparation, the capacity to autonomously acquire and develop knowledge, to shape information, and social skills will therefore receive the majority of attention. In light of this, the article's primary goal is to examine the key components of cutting-edge pedagogical technologies in the educational system.